Temperatura do solo, a 2cm de profundidade, como resposta à temperatura do ar - Rodrigues de Oliveira , Francisco; Sediyama, Gilberto C; Vieira , Manoel; Borges Pinheiro Filho , José (Revista Ceres, 2025)
Daily mean air temperature (TA) and soil temperature taken at two centimeters depth (TS) over a period of five years (1971 to 1975), in Viçosa, MG, were used to generate a finite series of Fourier coefficients, calculated by numerical integration and rectangular rule.